The Transcription Factor Egr3 Is a Putative Component of the Microtubule Organizing Center in Mouse Oocytes - Shin, Hyejin; Kwon, Sojung; Song, Haengseok; Lim, Hyunjung Jade (PLOS ONE, 2014)
The early growth response (Egr) family of zinc finger transcription factors consists of 4 members. During an investigation of Egr factor localization in mouse ovaries, we noted that Egr3 exhibits a subcellular localization that overlaps with the meiotic spindle in oocytes. Using Egr3-specific antibodies, we establish that Egr3 co-localizes with the spindle and cytosolic microtubule organizing centers (MTOCs) in oocytes during meiotic maturation. Notably, the Egr3 protein appears to accumulate around γ-tubulin in MTOCs. Nocodazole treatment, which induces microtubule depolymerization, resulted in the disruption of spindle formation and Egr3 localization, suggesting that Egr3 localization is dependent on the correct configuration of the spindle. Shortly after warming of vitrified oocytes, growing arrays of microtubules were observed near large clusters of Egr3. An in vitro microtubule interaction assay showed that Egr3 does not directly interact with polymerized microtubules. Egr3 localization on the spindle was sustained in early preimplantation mouse embryos, but this pattern did not persist until the blastocyst stage. Collectively, our result shows for the first time that the Egr3 a transcription factor may play a novel non-transcriptional function during microtubule organization in mouse oocytes.